2018
DOI: 10.1186/s12889-017-5003-3
|View full text |Cite
|
Sign up to set email alerts
|

Youth with chronic health problems: how do they fare in main-stream mentoring programs?

Abstract: BackgroundYouth with chronic physical health problems often experience social and emotional problems. We investigate the relationship between participation in the Big Brothers Big Sisters of Canada community-based mentoring programs (BBBS) and youth social and mood outcomes by youth health status.MethodsYouth newly enrolled in BBBS were classified by health status (one or more chronic physical health problems without activity limitation, n = 191; one or more chronic physical health problems with activity limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Our findings showed that mentees reported higher levels of general self-esteem after seven months, whereas a decrease over time was detected in students not involved in the program. Therefore, in line with previous findings (e.g., Kolar & McBride, 2011;Liang, Lund, Desiliva Mousseau, & Spencer, 2016;Lipman, DeWit, DuBois, Larose, & Erdem, 2018) the results of the present study suggest that the Mentor-UP program was effective in promoting self-esteem in mentees. In other terms, it is more probable to observe an increase in self-esteem among mentees than among the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings showed that mentees reported higher levels of general self-esteem after seven months, whereas a decrease over time was detected in students not involved in the program. Therefore, in line with previous findings (e.g., Kolar & McBride, 2011;Liang, Lund, Desiliva Mousseau, & Spencer, 2016;Lipman, DeWit, DuBois, Larose, & Erdem, 2018) the results of the present study suggest that the Mentor-UP program was effective in promoting self-esteem in mentees. In other terms, it is more probable to observe an increase in self-esteem among mentees than among the control group.…”
Section: Discussionsupporting
confidence: 92%
“…A possible explanation for this result is that some specific features of mentoring programs (such as, mentor engagement, family and school involvement, and community exploration) foster the development of mentees' self-esteem. For example, mentors dedicating ample time and energy to understanding the specific needs and resources of their mentees and accordingly selecting joint activities are more likely to be effective in increasing mentees' general self-esteem (Lee et al, 2015;Lipman et al, 2018). Indeed, when mentors are very flexible and easily accessible to the mentee, they can monitor their progress, give positive feedback, and plan future activities according to their new attitudes and tastes.…”
Section: Discussionmentioning
confidence: 99%